Excitation of vertical breathing motion in disc galaxies by tidally-induced spirals in fly-by interactions. Issue 1 (18th August 2022) - Kumar, Ankit; Ghosh, Soumavo; Kataria, Sandeep Kumar; Das, Mousumi; Debattista, Victor P
ABSTRACT: It is now clear that the stars in the Solar neighbourhood display large-scale coherent vertical breathing motions. At the same time, Milky Way-like galaxies experience tidal interactions with satellites/companions during their evolution. While these tidal interactions can excite vertical oscillations, it is still not clear whether vertical breathing motions are excited directly by the tidal encounters or are driven by the tidally-induced spirals. We test whether excitation of breathing motions are directly linked to tidal interactions by constructing a set of N -body models (with mass ratio 5:1) of unbound single fly-by interactions with varying orbital configurations. We first reproduce the well-known result that such fly-by interactions can excite strong transient spirals (lasting for ${\sim}2.9{-}4.2\, {\rm Gyr}$ ) in the outer disc of the host galaxy. The generation and strength of the spirals are shown to vary with the orbital parameters (the angle of interaction, and the orbital spin vector). Furthermore, we demonstrate that our fly-by models exhibit coherent breathing motions whose amplitude increases with height. The amplitudes of breathing motions show characteristic modulation along the azimuthal direction with compressing breathing motions coinciding with the peaks of the spirals and expanding breathing motions falling in the inter-arm regions – a signature of a spiral-driven breathing motion. These breathing motions in our models end when the strong tidally-induced spiral arms fade away. Thus, it is the tidally-induced spirals which drive the large-scale breathing motions in our fly-by models, and the dynamical role of the tidal interaction in this context is indirect.